Filsafat Konstruktivisme dalam Mengembangkan Calon Pendidik pada Implementasi Merdeka Belajar di Sekolah Kejuruan - Annisa Tishana; Dio Alvendri; Arief J. Pratama; Nizwardi Jalinus; Rijal Abdullah (Journal on Education, 2023)
The development of the business and industrial world (DUDI) demands an increase in hard skills, creativity and critical thinking from school graduates, including graduates of Vocational Schools. One of the efforts to achieve this is by implementing an freedom of Learn, where the learning process is constructivism which means student-centered learning. Furthermore, the understanding of a prospective educator related to the constructivism philosophy contained in the concept of independent learning must be improved first. This article will explain the philosophy of constructivism in the concept of freedom of Learn to develop understanding of prospective educators so they can implement it in vocational school learning. In this study the authors used the library research method, aiming to explore and collect relevant information and data from various sources obtained such as textbooks, dissertations, theses, research journals, research reports, documents of scientific discussion results, etc. Constructivism is defined as learning that emphasizes that knowledge is self-construction. Constructivism has an understanding of learning that emphasizes process rather than results and has the principle of student-centered learning, the teacher is only a facilitator and students discover more for themselves. This is very much in line with independent learning, students have the freedom to determine the knowledge they need by emphasizing the learning process. Prospective educators have an important role to play in building the competencies needed by students, these competencies are the 4C skills (critical thinking, communication, collaboration, creativity). Education that applies 4C skills and provides independence in thinking, digging for the truth, reasoning critically and seeing phenomena in students will form students with superior character who have adaptive abilities and are ready to face the industrial world.